2022
DOI: 10.15252/embr.202154234
|View full text |Cite
|
Sign up to set email alerts
|

ALS ‐linked KIF5A ΔExon27 mutant causes neuronal toxicity through gain‐of‐function

Abstract: Mutations in the human kinesin family member 5A (KIF5A) gene were recently identified as a genetic cause of amyotrophic lateral sclerosis (ALS). Several KIF5A ALS variants cause exon 27 skipping and are predicted to produce motor proteins with an altered C‐terminal tail (referred to as ΔExon27). However, the underlying pathogenic mechanism is still unknown. Here, we confirm the expression of KIF5A mutant proteins in patient iPSC‐derived motor neurons. We perform a comprehensive analysis of ΔExon27 at the singl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 67 publications
1
25
0
Order By: Relevance
“…An in vitro study has found that oligomerization occurs mostly by KIF5A rather than KIF5B and KIF5C [ 44 ]. It has been suggested that some unknown proteins could bind to the abnormal C-terminus of KIF5A (∆exon27) and trigger hyperactivation and aggregation, which changes cellular metabolisms and causes neuronal death [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study has found that oligomerization occurs mostly by KIF5A rather than KIF5B and KIF5C [ 44 ]. It has been suggested that some unknown proteins could bind to the abnormal C-terminus of KIF5A (∆exon27) and trigger hyperactivation and aggregation, which changes cellular metabolisms and causes neuronal death [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a perspective, it would be highly relevant to investigate how the condensation of motor proteins, through multivalent interactions, may contribute to physiological or pathological mechanisms. For instance, a recent study demonstrated that the ALS‐linked KIF5A ΔExon27 mutant, which enhances multimeric self‐interactions of KIF5A proteins, leads to its accumulation in neurotoxic micrometric aggregates localized at the cell periphery (Pant et al , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that an ALS-causing mutation of KIF5A is a gain-of-function mutation disrupting autoinhibition (Baron et al, 2022;Nakano et al, 2022;Pant et al, 2022). In A. nidulans, kinA K895 * or kinA -GFP is also a gain-of-function mutation affecting dynein-mediated early endosome transport in the presence of wild-type kinA (Fig.…”
Section: Kinesin-1 Autoinhibition Facilitates Cargo Adaptor-mediated ...mentioning
confidence: 98%
“…As dynein defects are linked to ALS (Chevalier-Larsen and Holzbaur, 2006; Liu and Henty-Ridilla, 2022), a defect in dynein-mediated transport could possibly contributes to the KIF5A-mutation-caused ALS. It is worthwhile to test this idea and other potential factors including aggregation of uninhibited kinesins or possible changes of microtubules (Baron et al, 2022;Budaitis et al, 2022;Chiba et al, 2022;Kawano et al, 2022;Nakano et al, 2022;Pant et al, 2022).…”
Section: Kinesin-1 Autoinhibition Facilitates Cargo Adaptor-mediated ...mentioning
confidence: 99%
See 1 more Smart Citation